Evaluación de la distribución poblacional de la tabebuia chrysantha en el área de restauración pasiva de la reserva ecológica Arenillas - Macas Vargas, Gisella Rosibel (2016)
The objectives of the research are aimed at obtaining basic information, which arises from the need for an evaluation of the population distribution of the Tabebuia chrysantha in the passive restoration area of ​​the Arenillas Ecological Reserve. The methodology used was vegetation sampling, 8 quadrants of 25 x 25 m were performed at different strategic points of the passive restoration area, in which the following parameters were considered: total tree height, CAP chest height circumference, DAP Diameter chest height equivalent to 1.30 m as standard measure and basal area obtained with the following formula, 0.0796 * CAP m2. The areas with the highest number of individuals were in the quadrants: Destacamento Chiriboga 18 and Pica telefonica 43, located in the north, and the quadrants: Los Pozos 17 and Cubo. Cabo de Vaca 24 in the south. The proposal. Contribution of Tabebuia chrysantha to carbon storage within REAR is an environmental service whose purpose is the conservation of the natural area, the dry forest being a natural barrier against the expansion of the Tumbesian desert. The data obtained in the evaluation were used in the estimation of biomass, carbon capture and economic value, using the indirect method considering that the study area is in the National System of Protected Areas SNAP.